Key access and utilization descriptors for lentil genetic resources - Bioversity International; International Center for Agricultural Research in the Dry Areas; National Bureau of Plant Genetic Resources (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for lentil utilization.